Measuring the Behavior and Preference for Energy Saving and Household Carbon Emission Reduction of Urban Residents in Bangkok and Its Vicinities, Thailand - PAWINEE IAMTRAKUL; Sararad Chayphong (Lowland Technology International, 2020)
Climate change has become a crisis situation worldwide with great importance attached to mitigation policy and implementation plans towards urban sustainability challenges. Together with rapid growth of urban environments, the Urban Heat Island (UHI) has significantly influenced temperature records whereby the concentration of urban structures and human activity results in a higher air temperature over urbanized areas, especially the metropolitan area of Bangkok, and its vicinity, Thailand. This research aimed to assess the behavior and preferences for energy saving and household carbon emission reduction by focusing on residential groups with a survey via face to face interviews. Data from three parts of questionnaires were input into Structural Equation Modeling (SEM) which are; 1) residential location and characteristics of neighborhood zone; 2) energy consumption behavior and carbon dioxide emission activity, and 3) attitudes toward the effects of UHI and Carbon Dioxide emission reduction. The results revealed that residents’ attitudes influenced their in-house behavior, workplace behavior and travel behavior. Therefore, by raising public awareness on self-adaptive behavior with more practical knowledge aligned with residents’ attitude towards daily activity and lifestyle could be potentially recommended for heat island mitigation measures wherever possible, especially in areas where community planning can be implemented.